Soil-Structure Interaction Under The Effect of High Groundwater Table - Duran, İlhan Burak (My University, 2017)
This paper gives an account of a study performed for the raft foundation of a commercial building of considerable height and area. A raft 175 m long was designed without due consideration to the buoyancy effect due to high groundwater table as the building is near the sea. Although the raft was designed as an uninterrupted system, the designer used different, and insufficient, thicknesses for the foundation in order to lower costs. A 3D study was subsequently undertaken to analyze the settlements of the raft using finite elements. There was reasonable agreement between the computed and the measured settlements. However, the front block of the raft was observed to float as soon as pumping for lowering of the groundwater table was halted. This instigated the analyzers to tie this portion of the raft to the surrounding piled curtain that was used for excavation of the foundation pit, by means of reinforced concrete beams. The computations show that the heave of the floor was restrained at acceptable levels. It is planned to stop pumping in the near future and compare the computed and measured vertical movements.
Keywords: Finite Element; Raft; 3D Analysis; Buoyancy; Settlement